Resistant Hypertension: Where are We Now and Where Do We Go from Here? - Pathan MK; Cohen DL (Dove Medical Press, 2020)
Mansur K Pathan, Debbie L Cohen Perelman School of Medicine at the University of Pennsylvania, Renal, Electrolyte and Hypertension Division, Philadelphia, PA 19104, USACorrespondence: Debbie L Cohen; Mansur K PathanPerelman School of Medicine at the University of Pennsylvania, Renal, Electrolyte and Hypertension Division, 1 Founders Building, 3400 Spruce Street, Philadelphia, PA 19104, USATel + 1 215-615-0794Email debbie.cohen@pennmedicine.upenn.edu; mansur.pathan@pennmedicine.upenn.eduAbstract: Resistant hypertension is an important subtype of hypertension that leads to an increased risk of cerebrovascular, cardiovascular, and kidney disease. The revised guidelines from the American College of Cardiology and American Heart Association now define resistant hypertension as blood pressure that remains above goal despite use of three maximally titrated anti-hypertensive medications including a diuretic or as a hypertensive patient who requires 4 or more agents for adequate BP control. These agents typically include a calcium-channel blocker, a renin-angiotensin system inhibitor, and a diuretic at maximal or maximally tolerated doses. As recognition of resistant hypertension increases, it is important to distinguish pseudo-resistant or apparent hypertension from true resistant hypertension. Etiologies of apparent resistant hypertension include measurement error and medication non-adherence. The prevalence of true resistant hypertension is likely much lower than reported in the literature when accounting for patients with apparent resistant hypertension. Evaluation of patients with true resistant hypertension includes screening for causes of secondary hypertension and interfering medications. Successful management of resistant hypertension includes lifestyle modification and optimization of medical therapy, often including the use of mineralocorticoid receptor antagonists. Looking ahead at developments in hypertension management, a slew of new device-based therapies are under active development. Of these, renal denervation is the closest to routine clinical application. Further study is needed before these devices can be recommended in the routine treatment of resistant hypertension.Keywords: resistant hypertension, pseudo-resistant hypertension, apparent resistant hypertension, masked hypertension